2011
DOI: 10.1002/acr.20600
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of dexamethasone iontophoresis for temporomandibular joint involvement in juvenile idiopathic arthritis

Abstract: Objective Temporomandibular joint (TMJ) involvement is common in Juvenile Idiopathic Arthritis (JIA). Dexamethasone iontophoresis (DIP) uses low-grade electric currents for transdermal dexamethasone delivery into deeper anatomic structures. The purpose of this study was to assess the safety and effectiveness of DIP for the treatment of TMJ involvement in JIA, and to delineate variables that are associated with improvement after DIP. Methods Medical records of all JIA patients who underwent DIP for TMJ involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 26 publications
0
18
0
2
Order By: Relevance
“…Pain did not improve and side effects ranged from transient erythema (86%) to metallic taste (4%) and blistering (4%). 67 Another study found that dexamethasone applied to the TMJ can help improve function but does not reduce pain. 68 Other investigations have shown that iontophoresis with dexamethasone is no more effective than a saline placebo in providing pain relief for patients with TMD.…”
Section: Modalitiesmentioning
confidence: 99%
“…Pain did not improve and side effects ranged from transient erythema (86%) to metallic taste (4%) and blistering (4%). 67 Another study found that dexamethasone applied to the TMJ can help improve function but does not reduce pain. 68 Other investigations have shown that iontophoresis with dexamethasone is no more effective than a saline placebo in providing pain relief for patients with TMD.…”
Section: Modalitiesmentioning
confidence: 99%
“…The hope is that early aggressive therapy of TMJ arthritis in children with JIA will help to prevent progressive destructive disease. Several groups have reported benefit of the use of intraarticular () and transcutaneous () long‐acting corticosteroids for treating TMJ arthritis in children with JIA, and more recently intraarticular infliximab has been explored in cases of refractory TMJ arthritis (). Measuring the benefit of therapy for TMJ arthritis in children with JIA has relied on mouth opening distances, patient‐reported pain and function, and MRI findings ().…”
Section: Introductionmentioning
confidence: 99%
“…The study involved 28 (2-21 y) JIA patients, most of whom completed the 8-10 iontophoresis sessions. Approximately 2/3 of the subjects experienced an improvement or a normalization of the temporomandibular joint range of motion and the associated pain [167]. While this small study suggests that dexamethasone iontophoresis is safe and effective, further studies are required to determine the optimum dosing and to compare iontophoresis with intra-articular steroid injections.…”
Section: Innovative Methods For Paediatric Transdermal Drug Deliverymentioning
confidence: 99%
“…The iontophoresis of dexamethasone phosphate, a common procedure in physiotherapy, was recently tested for the treatment of temporomandibular joint involvement in juvenile idiopathic arthritis (JIA) as a less invasive alternative to intra-articular steroid injections [167]. The study involved 28 (2-21 y) JIA patients, most of whom completed the 8-10 iontophoresis sessions.…”
Section: Innovative Methods For Paediatric Transdermal Drug Deliverymentioning
confidence: 99%